Dental Floss Prescription Pattern among the Dental Interns of Nepal - Pandey, Nashib (JNMA J Nepal Med Assoc, 2020)
INTRODUCTION: Periodontal disease is regarded as one of the preventable diseases. It can be prevented through effective plaque control measures that require mechanical instrumentation with various surgical or non-surgical periodontal therapies as well as daily oral hygiene measures. Dental professionals must be competent enough to promote good oral health by educating patients with daily oral hygiene practice measures. In this regard, the study was designed to assess the knowledge, attitude, and practice behaviour for using as well as prescribing dental floss among the dental interns of Nepal. METHODS: An online questionnaire consisting of two sections; the first comprised of the sociodemographic and professional aspects and the second consisted of questions related to knowledge, attitude, and practice regarding the use of dental floss, and its prescription was prepared using Google forms and the link was shared. The data were analysed in Statistical Package for Social Sciences (SPSS) version 20 software. RESULTS: In this study, the participants were familiar with the dental floss, but many lacked awareness regarding its proper use. Ninety-nine (64.3%) of the participants personally used dental floss. Only six (3.9%) never prescribed it to their patients. Among those who prescribed, only 37 (25%) always demonstrated the techniques. CONCLUSIONS: The study indicated that many participants used dental floss, however, educating and recommending the patient about it was comparatively low. This emphasizes the need to increase the awareness and use of interdental aids among dental interns to provide good oral self-care practices for the patient.